Estimates of mass absorption cross sections of black carbon for filter-based absorption photometers in the Arctic - S. Ohata; T. Mori; Y. Kondo; S. Sharma; A. Hyvärinen; E. Andrews; P. Tunved; E. Asmi; J. Backman; H. Servomaa; D. Veber; K. Eleftheriadis; et al. (Atmospheric Measurement Techniques, 2021)
Long-term measurements of atmospheric mass concentrations of black carbon (BC) are needed to investigate changes in its emission, transport, and deposition. However, depending on instrumentation, parameters related to BC such as aerosol absorption coefficient ( b abs ) have been measured instead. Most ground-based measurements of b abs in the Arctic have been made by filter-based absorption photometers, including particle soot absorption photometers (PSAPs), continuous light absorption photometers (CLAPs), Aethalometers, and multi-angle absorption photometers (MAAPs). The measured b abs can be converted to mass concentrations of BC ( M BC ) by assuming the value of the mass absorption cross section (MAC; M BC = babs/ <svg:svg xmlns:svg="http://www.w3.org/2000/svg" width="29pt" height="14pt" class="svg-formula" dspmath="mathimg" md5hash="93c2a2385251a0658a2cfb15159de417"><svg:image xmlns:xlink="http://www.w3.org/1999/xlink" xlink:href="amt-14-6723-2021-ie00001.svg" width="29pt" height="14pt" src="amt-14-6723-2021-ie00001.png"/></svg:svg> MAC). However, the accuracy of conversion of b abs to M BC has not been adequately assessed. Here, we introduce a systematic method for deriving MAC values from b abs measured by these instruments and independently measured M BC . In this method, M BC was measured with a filter-based absorption photometer with a heated inlet (COSMOS). COSMOS-derived M BC ( M BC (COSMOS)) is traceable to a rigorously calibrated single particle soot photometer (SP2), and the absolute accuracy of M BC (COSMOS) has been demonstrated previously to be about 15 % in Asia and the Arctic. The necessary conditions for application of this method are a high correlation of the measured b abs with independently measured M BC and ...